Algal toxins in the Baltic blue mussel (Baltic Mytilus trossulus edulis) - Ahlgren, Maya (2021)
Algal toxins have been found to bioaccumulate and have a seasonal variation over the summer months in marine biota. This can impact the food web through trophic transfer and the potential of using blue mussels for aquaculture. In this study, Baltic blue mussels from the Hanö Bight and Nämdö Island were collected during consecutive weeks in July 2020 and analyzed for algal toxins, more specifically, brominated compounds. The results showed 20-40 times higher concentrations of 6-OH-BDE47 and ΣOH-PBDEs at Nämdö Island compared to the Hanö Bight. The 2,4,6-TBP results showed similar concentrations at both locations, between 160-270 pg g-1 wet weight. The highest concentration of 6-OH-BDE47 measured approximately 6 000 pg g-1 wet weight and above 41 000 pg g-1 wet weight of ΣOH-PBDEs during the 3rd week at Nämdö Island. These concentrations are in line with previous studies of algal toxins in blue mussels within the Baltic Sea, while the concentrations at the Hanö Bight were surprisingly low. The difference between the locations, as well as between the measured weeks, supports a spatiotemporal variation on a weekly basis within the Baltic Sea.